Spectrum allocation in cognitive radio networks using chaotic biogeography‐based optimisation. Issue 5 (1st September 2018) - Tegou, Thomas I.; Tsiflikiotis, Antonios; Vergados, Dimitrios D.; Siakavara, Katherine; Nikolaidis, Spiros; Goudos, Sotirios K.; Sarigiannidis, Panagiotis; Obaidat, Mohammad
Abstract : Cognitive radio networks are a promising technology for the improvement of the spectrum utilisation. The basic idea is to maximise the utilisation of the available spectrum by dynamically assigning available channels to secondary users. This problem known as the spectrum allocation problem is non‐deterministic polynomial‐time hard (NP‐hard). Chaotic biogeography‐based optimisation (CBBO) is a recently proposed evolutionary algorithm that can be applied to the above‐mentioned problem. The authors compare CBBO with other popular algorithms in different spectrum allocation problem cases. The results show that CBBO performs in general better or similar to the other algorithms.